Human Papillomavirus Detection in Head and Neck Squamous Cell Carcinomas at a Tertiary Hospital in Sub-Saharan Africa - Evans Aboagye; Francis Agyemang-Yeboah; Babatunde Moses Duduyemi; Christian Obirikorang (The Scientific World Journal)
Fewer studies have been done over the years to establish the association of human papillomavirus (HPV) with head and neck squamous cell carcinoma (HNSSC) within the subregions of sub-Saharan Africa, and thus this study was designed to investigate the presence of HPV in HNSCC at a tertiary hospital in Ghana, providing additional evidence on the need to explore similar studies in other subregions. A retrospective cross-sectional study was employed to investigate the presence of the DNA of HPV genotypes in HNSCC archived tissue. A total of 100 HNSCC cases were classified as suitable for HPV genotyping. HPV-DNA was detected in 18% of the HNSCC cases, with 17 being HPV-16 and 1 dual infection with HPV-16 and HPV-18. HPV was prevalent in 50% of oropharyngeal cancers, 27% of laryngeal cancers, and 23% of oral cavity cancers. HPV E6/E7 oncogenic DNA was found in 18% of the HNSCC cases, with HPV-16 being the predominant genotype present. The pattern of HPV association was similar to earlier reported studies, recording a higher prevalence in oropharyngeal cancers, followed by laryngeal cancers and oral cavity cancers.